Analysis, detection, and mitigation of attacks in cyber-physical systems - Liu, Hanxiao (Nanyang Technological University, 2021)
Cyber-Physical Systems (CPS) offer close integration among computational elements, communication networks, and physical processes. Such systems play an increasingly important role in a large variety of fields, such as manufacturing, health care, environment, transportation, defence, and so on. Due to the wide applications and critical functions of CPS, increasing importance has been attached to their security. In this thesis, we focus on the security of CPS by investigating vulnerability under cyber-attacks, providing detection mechanisms, and developing feasible countermeasures against cyber-attacks.